Internal Environment of the Organization and Strategic Choice in Cement Manufacturing Firms in Kenya - Koech, Koech; Mathenge, Paul; Mwangi, Elias (European Journal of Business and Strategic Management, 2022)
Purpose: The objective of this research is to look into the internal environment elements of the organization that have an impact on strategic choice in the Kenyan cement industry. Methodology: A descriptive research design was used. The target population consisted of six Kenyan cement manufacturing firms. To collect data, a census and a questionnaire were used. The collection tool was piloted prior to the actual study to determine its validity and reliability. The arithmetic standard deviation and mean were utilized to assess central tendency and dispersion. Findings: Research findings are expected to significantly inform cement manufacturing firms and accelerate infrastructural development in Kenya as well as East Africa. Organizational structure was also positively correlated at (r =.368 and P>0.05), indicating a positive relationship, and organizational culture was positively correlated at (r =.358 and P >0.05), indicating a positive (+ve) and significant relationship. At (r) =.597 and P>0.05, managerial leadership styles had the greatest positive influence on strategic choice. The results of the study on organizational resources and strategic choice in Kenyan cement manufacturing firms revealed a moderately positive relationship that was statistically significant (r=.436 and P>0.05). According to the study, organizational structure, culture, managerial leadership style, and resources all have a positive (+ve) and significant effect on strategic choice. Unique contribution to theory, practice and policy (recommendation): The research hopes to inform policy on the strategic importance of supporting and strengthening strategic choices through adapting dynamic organizational structures and implementation policies for Kenyan cement manufacturing and beyond. The study will further enable top management of Kenyan cement manufacturing firms unlock the value of their investment through effective strategic leadership. The study will help improve the management and development of strategic areas of capacity building and improve policies geared towards enhancing the strategic choice.